PEMANFAATAN BATU KARANG PECAH KABUPATEN MALUKU TENGGARA BARAT PROVINSI MALUKU SEBAGAI AGREGAT KASAR UNTUK BAHAN BETON NORMAL - , Edwin Rudy Huwae, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Maluku Tenggara Barat is one of 12 regencies in the Province of Maluku that was established based on Act Number 46, year 1999 with Saumlaki as the capital city. Topographically, the area consists of volcanic and coral reef islands (atoll) with mostly of mountains, hills areas and common land for the rest. Infrastructure development requires availability of qualified material, which is unavailable in the area. Coral reef is a natural potential that has not been exploited in large scale because there have not been any scientific studies to identify its quality, characteristic and technical natures. Focus of this study was the utilization of coral reef for normal concrete. The scope included the observation and testing on coral reef, sand beach and normal concrete. Crushed stone granule sizes used were 5-10 mm, 10-20 mm and 20-40 mm, with normal concrete mix composition of 1:2:3 and cement-water factor of 0.40, 0.50 and 0.60. Based on the comparison of cement, sand and crushed stone volume, specimens were made that consisted of 54 cylinders, 18 cubes and 18 beams. Results of the study showed that technical characteristics of crushed coral reef included 2.453 specific gravity, 2.518 SSD specific gravity, 2.629% water absorbance, 1.41gr/cm 3 aggregated unit weight, 18.45% aggregate hardness and 31.30% wear resistance. For beach sand, the vales were 2.73 specific gravity, 2.359 gr/cm 3 SSD specific gravity, 1.381 kg/cm 3 unit weight, 5.876% water absorbance, 1.05% mud content, and 0.07813% chloride ion content. Technical characteristics of normal concrete resulted in 2263,88-2315,93 kg/m 3 specifivc gravity, 0.4 average concrete compressive strength at 0.4 cement-water factor with 413.86 kg/m3 and 509.75 kg/m 3 cement content that resulted in 43.93 MPa and 42.15 MPa compressive strengths, respectively